MRgFUS subthalamotomy in Parkinson’s disease: an approach aimed at minimizing Lesion Volume - Marina Campins-Romeu; Rebeca Conde-Sardón; Isabel Sastre-Bataller; Carlos Morata-Martínez; Mireya Losada-López; José Luís León-Guijarro; Luis Raga-Rodríguez; Julia Pérez-García; Antonio Gutiérrez-Martín; Andrés M. Lozano; Raquel Baviera-Muñoz; Irene Martínez-Torres (npj Parkinson's Disease)
Abstract Idiopathic Parkinson’s Disease (PD) is a neurodegenerative disorder characterized by tremor, rigidity, bradykinesia, and postural instability. Magnetic Resonance-guided high-intensity focused ultrasound (MRgFUS) of the subthalamic nucleus (STN) is gaining recognition as a minimally invasive surgical option. This study assesses the safety and efficacy of unilateral MRgFUS subthalamotomy, aiming to create the smallest effective lesion. Between June 2021 and October 2023, twelve PD patients underwent the procedure, with primary outcomes focused on safety and motor improvements after six months. Results indicated significant motor improvements, with over 50% reduction in tremor, rigidity, and bradykinesia, while balance and gait remained stable. Quality of life also improved. Side effects were generally mild and transient, though some patients experienced involuntary movements, managed through medication adjustments. Despite limitations, this technique appears to offer a promising, less-invasive alternative for managing PD symptoms with a favorable risk-benefit profile. Further research is necessary to refine the procedure and assess long-term outcomes.